All-solid-state battery cell, solid electrolyte powder, method for manufacturing solid electrolyte powder, and method for manufacturing coated body

A solid electrolyte powder composed of Li, Nb, and P coats the positive electrode in all-solid-state batteries, addressing interfacial resistance issues and enhancing conductivity and voltage stability.

JP2025001633APending Publication Date: 2025-01-08DOWA HOLDINGS CO LTD

Patent Information

Application Number
JP2024063138
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-20
Filing Date
2024-04-10
Publication Date
2025-01-08

AI Technical Summary

Technical Problem

All-solid-state batteries face issues with increased interfacial resistance due to reactions between the positive electrode active material and the solid electrolyte, particularly when sulfide-based electrolytes are used, which reduces battery performance such as capacity.

Method used

A solid electrolyte powder with specific compositions of Li, Nb, and P is used to coat the positive electrode active material, forming a protective layer that prevents reaction with the solid electrolyte, maintaining high lithium ion conductivity and decomposition voltage.

Benefits of technology

The solution achieves both high lithium ion conductivity and high decomposition voltage, improving battery performance by reducing interfacial resistance and enhancing energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001633000001_ABST
    Figure 2025001633000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a solid electrolyte powder capable of achieving both high lithium ion conductivity and high decomposition voltage, and achieve both high lithium ion conductivity and high decomposition voltage by using the solid electrolyte powder.SOLUTION: The present invention provides a solid electrolyte powder and related technologies thereof, which contains 0.7 to 5 mass% Li, 8 to 60 mass% Nb, and 1.0 to 30 mass% P relative to the solid electrolyte powder, with the content of non-oxygen remainder other than oxygen (O) being 10 mass% or less relative to the solid electrolyte powder, and has a crystallite diameter of 100 nm or less.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state battery cell, a solid electrolyte powder, a method for producing a solid electrolyte powder, and a method for producing a coating. [Background technology]

[0002] In an all-solid-state lithium-ion secondary battery (hereinafter sometimes referred to as an "all-solid-state battery"), a solid electrolyte is placed between a positive electrode active material and a negative electrode active material as a separator, and lithium ions are conducted between the two active materials via the solid electrolyte. Various solid electrolytes, such as sulfide-based, oxide-based, and polymer-based, have been developed, but at present, sulfide-based solid electrolytes are considered to be advantageous in terms of ion conductivity and manufacturing costs.

[0003] In all-solid-state batteries, there is a problem that the interfacial resistance between the positive electrode active material and the solid electrolyte, which is the separator, increases, and the battery's performance, such as capacity, tends to decrease. This increase in interfacial resistance is believed to be mainly caused by the reaction between the positive electrode active material and the solid electrolyte, which forms high-resistance sites on the surface of the positive electrode active material, and is likely to be a problem when a sulfide-based solid electrolyte is used as the separator.

[0004] Therefore, attempts have been made to cover the surface of the positive electrode active material with a solid electrolyte as a protective material made of a lithium ion conductive oxide (a well-known example is LiNbO3) or a halide, in order to prevent the positive electrode active material from reacting with the solid electrolyte, which is the separator.

[0005] Claim 1 of Patent Document 1 discloses an all-solid-state lithium battery using a lithium ion conductive solid electrolyte as an electrolyte, characterized in that the lithium ion conductive solid electrolyte is mainly composed of a sulfide and the surface of the positive electrode active material is coated with a lithium ion conductive oxide.

[0006] Patent Document 2 describes the following: When the voltage of the working electrode of the electrochemical cell is swept toward the oxidation side, a current originating from a non-Faraday reaction not involving the transfer of electrons and a minute current originating from a side reaction of water adsorbed on the surface of the conductive additive or impurities flows. Then, an excessive current begins to flow due to the oxidative decomposition of the solid electrolyte. In the test example described in Patent Document 2, the voltage at which a current value of 3 μA or more begins to flow is defined as the oxidative decomposition voltage. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] WO2007 / 004590 Brochure [Patent Document 2] WO2020 / 174868 Brochure Summary of the Invention [Problem to be solved by the invention]

[0008] In recent years, there has been an increasing demand for improved output characteristics and energy density of all-solid-state batteries. Therefore, there is a demand for solid electrolytes that have high lithium ion conductivity and high decomposition voltage. This decomposition voltage refers to the oxidative decomposition voltage as described in Patent Document 2.

[0009] Solid electrolytes as protective materials deteriorate when a high charging voltage is applied. In the case of LiNbO3, a typical protective material described in Patent Document 1, deterioration accelerates when the charging voltage exceeds 4.45 V. In other words, in the case of LiNbO3, a typical protective material described in Patent Document 1, deterioration accelerates when the decomposition voltage exceeds about 4.45 V.

[0010] An object of the present invention is to provide a solid electrolyte powder that can achieve both high lithium ion conductivity and high decomposition voltage, a method for producing the same, and a method for producing a coating body thereof. Another object of the present invention is to provide an all-solid-state battery cell that uses the solid electrolyte powder or a coating thereof, thereby achieving both high lithium ion conductivity and high decomposition voltage. [Means for solving the problem]

[0011] The first invention is A conductive material on a high potential side; a first solid electrolyte in contact with the high potential side conductive material; a second solid electrolyte in contact with the first solid electrolyte; a conductive material on a low potential side in contact with the second solid electrolyte; Equipped with The first solid electrolyte contains at least one of the following solid electrolytes (1) and (2) as a main component: The second solid electrolyte is an all-solid-state battery cell containing a sulfide as a main component. (1) A solid electrolyte comprising 0.7 to 5 mass% Li, 8 to 60 mass% Nb, and 1.0 to 30 mass% P, the content of non-oxygen remainder other than oxygen (O) being 10 mass% or less relative to the solid electrolyte, and the crystallite size being 100 nm or less. (2) A solid electrolyte in which, when the molar ratio of Li, Nb, and P contained in the solid electrolyte is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, and z is 5 to 65, and the crystallite size is 100 nm or less.

[0012] The second invention is The first solid electrolyte is an all-solid-state battery cell according to the first invention, which is the following (3) and (4). (3) The solid electrolyte contains 0.7 to 2.6 mass% Li, 8 to 60 mass% Nb, and 2.0 to 30 mass% P, A solid electrolyte, in which, when the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 30 or less, the content of non-oxygen remainder other than oxygen (O) is 10 mass% or less relative to the solid electrolyte, and the crystallite size is 100 nm or less. (4) A solid electrolyte, in which the molar ratio of Li, Nb, and P contained in the solid electrolyte is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 30, y is 5 to 65, and z is 5 to 65, and the crystallite size is 100 nm or less.

[0013] The third invention is the high potential side conductive material includes a positive electrode active material and other conductive members, The all-solid-state battery cell according to the first or second invention, wherein the positive electrode active material and the first solid electrolyte are in contact with each other, and the positive electrode active material and the second solid electrolyte are not in contact with each other.

[0014] The fourth invention is the high potential side conductive material includes a positive electrode active material and other conductive members, The all-solid-state battery cell according to any one of the first to third aspects of the present invention, wherein the surfaces of particles of the positive electrode active material are coated with the first solid electrolyte.

[0015] The fifth invention is The solid electrolyte powder contains 0.7 to 5 mass% Li, 8 to 60 mass% Nb, and 1.0 to 30 mass% P, The content of the non-oxygen remainder other than oxygen (O) in the remainder is 10 mass% or less with respect to the solid electrolyte powder, This is a solid electrolyte powder with a crystallite size of 100 nm or less.

[0016] The sixth invention is The solid electrolyte powder contains 0.7 to 2.6 mass% Li, 8 to 60 mass% Nb, and 2.0 to 30 mass% P, The solid electrolyte powder according to the fifth invention, wherein x is 30 or less when the molar ratio of Li, Nb and P is Li:Nb:P=x:y:z (x+y+z=100).

[0017] The seventh invention is In the solid electrolyte powder according to the fifth or sixth invention, the content of the transition metal element in the non-oxygen remainder is 3 mass % or less based on the solid electrolyte powder.

[0018] The eighth invention is When the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 15-50, y is 5-65, and z is 5-65. This is a solid electrolyte powder with a crystallite size of 100 nm or less.

[0019] The ninth invention is In the solid electrolyte powder according to an eighth aspect of the present invention, the content of the non-oxygen remainder other than oxygen (O) in the remainder is 10 mass % or less based on the mass of the solid electrolyte powder.

[0020] The tenth invention is The solid electrolyte powder according to the eighth or ninth invention, wherein x is 15-30, y is 5-65, and z is 5-65.

[0021] The eleventh invention is In the solid electrolyte powder according to the present embodiment, the total mass percentage of Li, Nb, and P is in the range of 25 to 65 mass percent.

[0022] The twelfth invention is The solid electrolyte powder according to any one of the fifth to eleventh aspects of the present invention has a particle size, that is, a volume-based cumulative 50% particle size (D50) obtained by a laser diffraction / scattering particle size distribution measuring device, of 5 to 50 μm.

[0023] The thirteenth invention is The solid electrolyte powder according to any one of the fifth to twelfth aspects of the present invention is for use in an all-solid-state battery cell.

[0024] The fourteenth invention is A conductive material on a high potential side; a first solid electrolyte in contact with the high potential side conductive material; a second solid electrolyte in contact with the first solid electrolyte; a conductive material on a low potential side in contact with the second solid electrolyte; Equipped with The first solid electrolyte contains the solid electrolyte powder according to any one of the fifth to thirteenth aspects of the present invention as a main component, The second solid electrolyte is an all-solid-state battery cell containing a sulfide as a main component.

[0025] The fifteenth invention is A method for producing a solid electrolyte powder according to the fifth or eighth aspect of the present invention, A step of dry-mixing a Li raw material, a Nb raw material, and a P raw material in an inert atmosphere having a dew point of −20° C. or less to obtain a mixed powder; A firing step of firing the mixed powder at 350° C. or less in an air atmosphere; The present invention relates to a method for producing a solid electrolyte powder having the above structure.

[0026] The sixteenth invention is A fifteenth aspect of the present invention provides a method for producing a solid electrolyte powder, wherein the Li raw material is lithium oxide, the Nb raw material is niobium oxide hydroxide, and the P raw material is diphosphorus pentoxide.

[0027] The seventeenth invention is a phosphate ion adding step of adding phosphate ions to an aqueous solution containing niobium polyacid ions and lithium; a drying step of drying the aqueous solution obtained by the adding step to obtain a solid electrolyte powder; having This is a method for producing a solid electrolyte powder, in which the molar ratio of Li, Nb, and P in the aqueous solution obtained by the adding step is Li:Nb:P=x:y:z (x+y+z=100), where x is 15 to 50, y is 5 to 65, and z is 5 to 65.

[0028] The eighteenth invention is adding phosphate ions to an aqueous solution containing niobium polyphosphate ions and lithium to obtain an aqueous solution in which, when the molar ratio of Li, Nb, and P in the aqueous solution is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, and z is 5 to 65; a coating step of contacting the aqueous solution obtained by the above step with a positive electrode active material to coat the surface of the positive electrode active material with a solid electrolyte; having The method for producing a coating body for the solid electrolyte satisfies at least one of the following: i) the solid electrolyte contains 0.7 to 5 mass% Li, 8 to 60 mass% Nb, and 1.0 to 30 mass% P; The content of the non-oxygen remainder other than oxygen (O) in the remainder is 10 mass% or less with respect to the solid electrolyte, A solid electrolyte with a crystallite size of 100 nm or less. ii) When the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 15-50, y is 5-65, and z is 5-65; A solid electrolyte with a crystallite size of 100 nm or less. Effect of the Invention

[0029] According to the present invention, it is possible to provide a solid electrolyte powder that can achieve both high lithium ion conductivity and high decomposition voltage, a method for producing the same, and a method for producing a coating body thereof. Furthermore, according to the present invention, by using the solid electrolyte powder or a coating thereof, it is possible to provide an all-solid-state battery cell that achieves both high lithium ion conductivity and high decomposition voltage. [Brief description of the drawings]

[0030] [Figure 1] FIG. 1 is a schematic diagram of a cross-sectional structure of one embodiment of an all-solid-state battery cell according to the present embodiment. [Diagram 2] FIG. 2 is a schematic diagram of a cross-sectional structure of another aspect of the all-solid-state battery cell according to the present embodiment. [Diagram 3] FIG. 3 is a schematic diagram of a cross-sectional structure of a lithium-ion secondary battery utilizing the all-solid-state battery cell according to this embodiment. [Figure 4] FIG. 4 is a flow diagram of a method for producing a solid electrolyte powder according to the present invention. [Diagram 5] FIG. 5 is a diagram showing the composition ratios of Li, Nb, and P in the solid electrolyte powder obtained in each example, expressed in molar ratio. [Figure 6]FIG. 6 is a diagram showing the composition ratios of Li, Nb, and P in the composition expressed by molar ratio of the solid electrolyte powder obtained in each example, as well as the decomposition voltage as numerical values. [Figure 7] FIG. 7 is a plot of the electrochemical evaluation in each example, with the horizontal axis representing the potential (unit: V (vsLi / Li+)) and the vertical axis representing the current value (unit: μA). [Figure 8] FIG. 8 is a plot of the evaluation of the degree of crystallinity in each example, with 2θ (unit: °) on the horizontal axis and intensity (cps) on the vertical axis. [Figure 9] FIG. 9 is a flow diagram when the first solid electrolyte is coated on the positive electrode active material using the coating liquid according to the present invention. [Figure 10] FIG. 10 is a diagram showing FT-IR spectra of the aqueous solutions obtained in Comparative Example 2 and Example 10. [Figure 11] FIG. 11 is a schematic diagram of the cross-sectional structure of an electrochemical cell constructed to examine the discharge DCR increase rate in Comparative Example 2 and Example 10. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] Hereinafter, an embodiment of the present invention will be described. The symbol "to" indicates a value greater than or equal to the specified value and less than or equal to the specified value.

[0032] In this specification, the term "high potential side" refers to a side of a high potential electrode (positive electrode in a battery) in a charge path relative to a solid electrolyte as a separator disposed between both electrodes. The term "low potential side" refers to a side of a low potential electrode (negative electrode in a battery) in a charge path relative to a solid electrolyte as a separator disposed between both electrodes.

[0033] This embodiment will be described in the following order. 1.Solid electrolyte powder 2. Solid-state battery cells 3. Lithium-ion secondary battery 4. Manufacturing method of solid electrolyte powder

[0034] [1. Solid electrolyte powder] The solid electrolyte powder according to this embodiment mainly has the following components. <Configuration 1> The solid electrolyte powder contains 0.7 to 5 mass% Li, 8 to 60 mass% Nb, and 1.0 to 30 mass% P. This configuration is also called "mass% expressed configuration." <Configuration 2> The content of the non-oxygen remainder other than oxygen (O) in the remainder is 10 mass % or less based on the solid electrolyte powder. <Configuration 3> The crystallite size is 100 nm or less.

[0035] Regarding the above-mentioned configuration 1, if the amount of Li (lithium) contained in the solid electrolyte powder is 0.7 mass% or more and 5.0 mass% or less, this is a sufficient amount as a carrier, and high lithium ion conductivity (hereinafter also referred to as ion conductivity) can be ensured. -11 S / cm or more, preferably 5.0×10 -10 The ionic conductivity of 0.1 S / cm or more can be ensured. The lower limit of the amount of Li contained in the solid electrolyte powder may be 1.0 mass%, 1.1 mass%, 1.2 mass%, 1.3 mass%, or 1.4 mass%. The upper limit of the amount of Li contained in the solid electrolyte powder may be 4.0 mass%, 3.5 mass%, or 2.6 mass%.

[0036] When the amount of Nb (niobium) contained in the solid electrolyte powder is 8% by mass or more and 60% by mass or less, the function as a solid electrolyte in a battery can be sufficiently exhibited. The upper limit of the amount of Nb contained in the solid electrolyte powder may be 55% by mass.

[0037] If the amount of P (phosphorus) contained in the solid electrolyte powder is 1.0 mass% or more and 30 mass% or less, the voltage resistance can be sufficiently improved. The lower limit of the amount of P contained in the solid electrolyte powder may be 2.0 mass%. The upper limit of the amount of P contained in the solid electrolyte powder may be 25 mass% or 20 mass%.

[0038] The decomposition voltage obtained by measuring an electrochemical cell made using the solid electrolyte powder having the following composition is 5.0 V or more, and the ionic conductivity is 5×10 -10 This is preferable because it is S / cm or more. "The solid electrolyte powder contains 0.7 to 2.6 mass% Li, 8 to 60 mass% Nb, and 2.0 to 30 mass% P, When the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 30 or less. The method for obtaining the decomposition voltage and ionic conductivity from the solid electrolyte powder will be described in detail in the Examples section. The detailed content is expressed as generally as possible in the above-mentioned Means for Solving the Problems section.

[0039] Regarding the above configuration 2, the content of elements other than O (ie, non-oxygen remainder) among the remainders other than Li, Nb, and P in the solid electrolyte powder is specified to be 10 mass % or less with respect to the solid electrolyte powder.

[0040] The abundance ratio (molar ratio) of oxygen is mainly determined by the valences of Li, Nb, and P. In other words, Li is +1, Nb is +5, P is +5, and oxygen is -2, and the amount of oxygen is determined so that the charge is compensated (this is the main amount of oxygen). The general formula is xLi2O-yNb2O5-zP2O5.

[0041] If the non-oxygen remainder contains elements other than Li, Nb, and P, the amount of oxygen can be calculated in the same way from the valence of the element (considered the secondary oxygen amount). The non-oxygen remainder can contain H, C, N, other metallic elements, semi-metallic elements, and non-metallic elements. For example, H comes from H2O, C comes from CO2, and N comes from N2O5.

[0042] The amount of oxygen (molar ratio) can be calculated from the sum of the amount of main oxygen and the amount of secondary oxygen, and the mass ratio of oxygen can be calculated by further mass conversion. The mass ratio of oxygen can also be measured by a known method such as an oxygen analyzer. This is particularly effective when the valence of the non-oxygen remaining element is unknown.

[0043] The above definition makes it clear that the majority (i.e., 90 mass% or more) of the solid electrolyte powder according to this embodiment is composed of Li, Nb, P, and O. The content of the non-oxygen remainder is preferably 5 mass% or less, and more preferably 1 mass% or less.

[0044] The content of transition metal elements (preferably all metal elements) in the non-oxygen remainder is preferably 3 mass % or less relative to the solid electrolyte powder.

[0045] The content of non-oxygen components can be measured by using a nitrogen analyzer for N (nitrogen) and a carbon-sulfur analyzer for C (carbon), and other elements can be measured by an inductively coupled plasma atomic emission spectrometry (ICP-AES). The total content (mass%) of elements other than Li, Nb, P, and O determined by these measurements is the non-oxygen remainder content.

[0046] A solid electrolyte powder containing Li, Nb, and P in amounts satisfying the above configuration 1 and having a crystallite size of 100 nm or less (i.e., satisfying the above configuration 3) achieves both high lithium ion conductivity and high decomposition voltage when processed into an all-solid-state battery cell, as shown in the Examples section below.

[0047] The configuration of the solid electrolyte powder according to this embodiment can also be expressed as follows. That is, in the solid electrolyte powder according to this embodiment, when the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, z is 5 to 65, and the crystallite size is 100 nm or less. This configuration related to x, y, and z is also called a "molar ratio expressed configuration."

[0048] When x is 15 or more and 50 or less, the amount is sufficient as a carrier, and high lithium ion conductivity (hereinafter also referred to as ionic conductivity) can be ensured. -11 An ionic conductivity of S / cm or higher can be ensured.

[0049] It is preferred that x is 30 or less.

[0050] When y is 5 or more and 65 or less, the function as a solid electrolyte in a battery can be sufficiently exhibited.

[0051] If z is 5 or more and 65 or less, the voltage resistance can be sufficiently improved.

[0052] The decomposition voltage obtained by measuring an electrochemical cell made using the solid electrolyte powder in which x is 15 to 30, y is 5 to 65, and z is 5 to 65 is 5.0 V or more, and the ionic conductivity is 5 × 10 -10 This is preferable because it is S / cm or more.

[0053] Regarding the above configuration 3, the crystallite diameter of the solid electrolyte powder is stipulated to be 100 nm or less.

[0054] The crystallite diameter of the solid electrolyte powder is determined by the Scherrer formula (Dhkl=Kλ / βcosθ) from the diffraction peak data observed in the region of 2θ: 15° to 40° by powder X-ray diffraction (XRD) measurement. The crystallite diameter is preferably 50 nm or less. More preferably, it is 30 nm or less. It is still more preferably an amorphous substance in which a halo X-ray chart is observed in the region of 2θ: 15° to 40°. Note that the "halo" is observed as a broad rise of gentle undulations of X-ray intensity that does not show a clear peak in the region of 2θ: 15° to 40° in the X-ray chart obtained by XRD measurement. The half-width of the halo is 2θ: 2° or more. When the crystallite diameter exceeds 100 nm and the solid electrolyte powder is no longer amorphous, the ionic conductivity is 5×10 -10 It drops to less than S / cm.

[0055] It is also preferable to combine the above molar ratio expression with the content of the above configuration 1 (i.e., expression in mass %). It is also preferable to combine the above molar ratio expression with the content of the above configuration 3.

[0056] The above expressions in mass % or molar ratios may be combined with the following configurations.

[0057] The molar ratio of P to Li (P / Li) in the solid electrolyte powder according to this embodiment is preferably 0.2 or more and 3.5 or less. From the viewpoint of voltage resistance, it is more preferably 1.4 or more and 3.5 or less. The molar ratio of P to Nb (P / Nb) in the solid electrolyte powder according to this embodiment is preferably 0.1 or more and 6.5 or less. From the viewpoint of voltage resistance, it is preferably 1.4 or more and 6.5 or less, more preferably 3.0 or more and 6.5 or less, and even more preferably 4.0 or more and 6.5 or less.

[0058] In the solid electrolyte powder according to this embodiment, the total mass percentage of Li, Nb, and P is preferably in the range of 25 to 65 mass percentage.

[0059] The particle size of the solid electrolyte powder according to the present embodiment is not particularly limited, but the volume-based cumulative 50% particle size (D50) obtained by measuring the volume-based particle size distribution using a laser diffraction scattering type particle size distribution measuring device is preferably 5 to 50 μm. From the viewpoint of ion conductivity, the volume-based cumulative 50% particle size (D50) is preferably 5 to 15 μm.

[0060] [2. All-solid-state battery cells] The all-solid-state battery cell according to this embodiment (in other words, the arrangement of the solid electrolyte) mainly has the following configuration. -Conductive material on high potential side A first solid electrolyte in contact with the conductive material on the high potential side A second solid electrolyte in contact with the first solid electrolyte. A conductive material on the low potential side that contacts the second solid electrolyte The contents overlapping with those explained in [1. Solid electrolyte powder] above will be omitted below.

[0061] FIG. 1 shows a schematic cross-sectional structure of one embodiment of an all-solid-state battery having an all-solid-state battery cell of the present invention. In this figure, the cell structure is extremely simplified in order to explain the positional relationship of each member. A high-potential side conductive material 3 and a low-potential side conductive material 4 face each other with a first solid electrolyte 1 and a second solid electrolyte 2, which is a separator, sandwiched therebetween. The first solid electrolyte 1 is interposed between the high-potential side conductive material 3 and the second solid electrolyte 2. There is a contact portion between the high-potential side conductive material 3 and the first solid electrolyte 1, and there is also a contact portion between the first solid electrolyte 1 and the second solid electrolyte 2.

[0062] In an all-solid-state battery, the conductive material 3 on the high potential side is usually composed of a positive electrode active material 31 and a conductive material 32 other than the positive electrode active material. The positive electrode active material 31 is an ion conductive material and a conductive material. There is no limitation on the form, and it may be in a particulate form or a powder form. The conductive material 32 other than the positive electrode active material is a current collector, a conductive assistant, etc. In an actual all-solid-state battery, the positive electrode material is generally composed of conductive members such as a current collector, a positive electrode active material, and a conductive assistant, as well as particles of an ion conductive material (solid electrolyte) mixed to fill the gaps between the particles of the positive electrode active material. The conductive material 3 on the high potential side in FIG. 1 is a schematic diagram illustrating the positional relationship of the part of such a positive electrode material that is composed of a conductive member with respect to the first solid electrolyte 1. In the illustrated embodiment, the positive electrode active material 31 and the first solid electrolyte 1 are in contact with each other, so that ion conduction between the second solid electrolyte 2, which is a separator, and the positive electrode active material 31 is performed via the first solid electrolyte 1. Furthermore, since the positive electrode active material 31 is in contact with the conductive material 32 other than the positive electrode active material, electrical conduction is ensured between the positive electrode active material 31 and an external wiring member (not shown) connected to the conductive material 32 other than the positive electrode active material.

[0063] Known substances can be used as the positive electrode active material 31, and new positive electrode active materials may also be developed and applied. Representative known positive electrode active materials include LiCoO2 (LCO type), LiNiO2 (LNO type), LiMn2O4 (LMO type), LiNiCoAlO2 (NCA type), LiNiCoMnO2 (NCM type), Li2MnO3-LiNiCoMnO2 (solid solution type), LiNiMnO4 (spinel type), LiMnFePO4 (phosphate type), Li2FeSiO4 (silicate type), and the like.

[0064] The first solid electrolyte 1 contains at least one of the following solid electrolytes (1) and (2) as a main component. (1) A solid electrolyte comprising 0.7 to 5 mass% Li, 8 to 60 mass% Nb, and 1.0 to 30 mass% P, the content of non-oxygen remainder other than oxygen (O) being 10 mass% or less relative to the solid electrolyte, and the crystallite size being 100 nm or less. (2) A solid electrolyte in which, when the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, and z is 5 to 65, and the crystallite size is 100 nm or less.

[0065] The term "main component" as used herein means that the total content of the constituent materials of the first solid electrolyte 1 is 50 mass % or more, which is a solid electrolyte that satisfies at least one of the conditions described in (1) and (2). The total content of the constituent materials of the first solid electrolyte 1 that satisfies at least one of the conditions described in (1) and (2) is preferably 80 mass % or more, and more preferably 90 mass % or more.

[0066] The solid electrolyte may be a powder as described above in [1. Solid electrolyte powder], but the solid electrolyte may be provided on the positive electrode in other forms (e.g., layered or film-like). Therefore, the term "solid electrolyte" is used in this section. However, for the sake of simplicity, hereinafter, solid electrolyte powder is used as an example.

[0067] It is preferable that the first solid electrolyte 1 further satisfies the following conditions (3) and (4). (3) The solid electrolyte contains 0.7 to 2.6 mass% Li, 8 to 60 mass% Nb, and 2.0 to 30 mass% P, A solid electrolyte, in which, when the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 30 or less, the content of non-oxygen remainder other than oxygen (O) is 10 mass% or less relative to the solid electrolyte, and the crystallite size is 100 nm or less. (4) A solid electrolyte, in which the molar ratio of Li, Nb, and P contained in the solid electrolyte is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 30, y is 5 to 65, and z is 5 to 65, and the crystallite size is 100 nm or less.

[0068] In the embodiment of FIG. 1, the first solid electrolyte 1 completely blocks the contact between the high-potential side conductive material 3 and the second solid electrolyte 2, which is a separator. Therefore, the members constituting the high-potential side conductive material 3 are protected from reactions resulting from contact with the second solid electrolyte 2, which mainly contains sulfides or the like. In other words, the first solid electrolyte 1 functions as a protective material. In addition, as described later, the first solid electrolyte 1 applied in the present invention has excellent resistance to deterioration when a high voltage is applied when it is placed in contact with the second solid electrolyte 2, which mainly contains sulfides or the like, so that the all-solid-state battery cell of the embodiment shown in FIG. 1 is effective in improving the decomposition voltage.

[0069] The second solid electrolyte 2 is composed mainly of sulfide from the viewpoints of ion conductivity and production costs, and functions as a separator. "Composed mainly of sulfide" means that the total content of sulfide in the constituent materials of the second solid electrolyte 2 is 50 mass % or more. The total content of sulfide in the constituent materials of the second solid electrolyte 2 is preferably 80 mass % or more, and more preferably 90 mass % or more.

[0070] The above sulfides can be any known substance with ionic conductivity, and new ionic conductive substances may also be developed. Representative known ionic conductive substances include Li6PS5Cl (crystal (argyrodite)), Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 (crystal), Li 10 GeP2S 12 (crystal), 30Li2S 26B2S3 44LiI (glass), 63Li2S 36SiS2 1Li3PO4 (glass), 57Li2S 38SiS2 5Li4SiO4 (glass), 70Li2S 30P2S5 (glass), Li7P3S 11 (glass ceramic), Li 3.25 P 0.95 S4 (glass ceramic) and others.

[0071] In an all-solid-state battery, the conductive material 4 on the low potential side is usually composed of a negative electrode active material 41 and a conductive material 42 other than the negative electrode active material. In an actual all-solid-state battery, the negative electrode material is generally composed of conductive members such as a current collector and a negative electrode active material, as well as particles of an ion conductive material (solid electrolyte) mixed to fill the spaces between the particles of the negative electrode active material. The conductive material 4 on the low potential side in FIG. 1 is a schematic diagram showing the arrangement of the part of such a negative electrode material that is composed of a conductive member relative to the second solid electrolyte 2. The configuration of the conductive material 4 on the low potential side and the arrangement of the conductive material 4 and the second solid electrolyte 2 can be the same as those of a known all-solid-state battery. Note that a third solid electrolyte may be arranged between the second solid electrolyte 2 and the conductive material 4 on the low potential side, if necessary.

[0072] In the embodiment of the all-solid-state battery shown in FIG. 1, the entire conductive material 3 on the high potential side is separated from the second solid electrolyte (such as a sulfide) which is the separator by the presence of the first solid electrolyte 1, so that the decomposition voltage can be improved without covering the surfaces of the particles of the positive electrode active material 31 with a solid electrolyte which is a protective material.

[0073] FIG. 2 shows a schematic cross-sectional structure of another embodiment of the all-solid-state battery cell of the present invention. In this figure, as in FIG. 1, the cell structure is extremely simplified in order to explain the positional relationship of each member. A high-potential side conductive material 3 and a low-potential side conductive material 4 face each other with a second solid electrolyte 2, which is a separator, sandwiched therebetween. The first solid electrolyte 1 is adjacent to the second solid electrolyte 2 and the high-potential side conductive material 3. In the embodiment of FIG. 2, among the members constituting the high-potential side conductive material 3, the positive electrode active material 31 is in contact with the first solid electrolyte 1 to avoid direct contact with the second solid electrolyte, and the conductive material 32 other than the positive electrode active material has a portion in direct contact with the second solid electrolyte 2 without the first solid electrolyte 1 being interposed therebetween. In addition, the first solid electrolyte 1 may completely cover the positive electrode active material 31 and not be in direct contact with the conductive material 32, but if the first solid electrolyte 1 is sufficiently thin, the positive electrode active material 31 and the conductive material 32 are in electrical contact with each other due to the tunnel effect, and the positive electrode active material 31 and the conductive material 32 are at the same potential. The rest of the structure is the same as that of the embodiment shown in FIG. 1 above.

[0074] 2, ion conduction between the second solid electrolyte 2, which is a separator, and the positive electrode active material 31 is performed via the first solid electrolyte 1. Therefore, in this embodiment, the first solid electrolyte 1 also functions as a protective material. Moreover, the positive electrode active material 31 is adjacent to a conductive material 32 other than the positive electrode active material at a surface portion not in contact with the first solid electrolyte 1, so that electrical conduction between the positive electrode active material 31 and an external wiring member (not shown) connected to the conductive material 32 other than the positive electrode active material is ensured.

[0075] Furthermore, when the first solid electrolyte is as thin as several tens of nm or less, electrons can overcome the potential barrier of the first solid electrolyte, ensuring electrical conduction between the positive electrode active material 31 and the conductive material 32. Therefore, there is no problem in terms of the battery structure even if the positive electrode active material 31 is completely covered with the first solid electrolyte 1.

[0076] 2, a case where a positive electrode active material powder is applied in which the particle surfaces of the positive electrode active material 31 are coated with a protective material, the first solid electrolyte 1, can be mentioned. In this case, in an actual all-solid-state battery, the contact portion between the positive electrode active material 31 and a conductive material 32 other than the positive electrode active material corresponds to a portion where particles of a conductive assistant (e.g., stainless steel or carbon) penetrate the protective material coating layer and are electrically conductive with the positive electrode active material 31.

[0077] As a special example, when the positive electrode active material powder is completely covered with the first solid electrolyte 1, if the thickness of the first solid electrolyte (layer) is as thin as several tens of nm or less, electrical conduction between the conductive assistant and the positive electrode active material is ensured by the tunnel effect, even without providing a contact portion as described above.

[0078] The ion-conducting material (solid electrolyte) filling the gaps between the particles of the positive electrode active material 31 conducts ions through a coating layer made of the first solid electrolyte 1 functioning as a protective material, so that the second solid electrolyte 2 (such as a sulfide) of the same type as the separator can be used as the ion-conducting material. In FIG. 2, the part of the second solid electrolyte 2 in contact with the first solid electrolyte 1 can be considered to correspond to the particles of the second solid electrolyte 2 as the positive electrode material filling the gaps between the particles of the positive electrode active material 31. The particles of the second solid electrolyte 2 are in contact with the particles of the second solid electrolyte 2 constituting the separator layer and are responsible for ion conduction. That is, the part of the reference symbol 2 shown in FIG. 2 corresponds to a collective description of the particles of the second solid electrolyte 2 as the separator and the particles of the second solid electrolyte 2 as the positive electrode material filling the gaps between the particles of the positive electrode active material 31.

[0079] In any case, it is preferable that the conductive material on the high potential side includes a positive electrode active material and other conductive members, the positive electrode active material is in contact with the first solid electrolyte, and the positive electrode active material is not in contact with the second solid electrolyte.

[0080] The all-solid-state battery cell according to this embodiment has a decomposition voltage of 4.5 V or more and an ionic conductivity of 5×10 -11Preferably, the decomposition voltage is 5.0 V or more and / or the ionic conductivity is 5×10 -10 S / cm or more.

[0081] [3. Lithium-ion secondary batteries] The technical concept of the present invention is also reflected in the lithium ion secondary battery using the all-solid-state battery cell according to this embodiment. A known configuration may be adopted as a specific configuration other than the all-solid-state battery cell in the lithium ion secondary battery (for example, FIG. 3).

[0082] [4. Method for producing solid electrolyte powder] <<Dry method for producing solid electrolyte powder>> FIG. 4 is a flow diagram of a method for producing a solid electrolyte powder according to the present invention. The method for producing a solid electrolyte powder (dry method) according to this embodiment mainly has the following configuration. A process to obtain a mixed powder by dry mixing Li, Nb, and P raw materials in an inert atmosphere with a dew point of -20°C or less. A sintering process for sintering the mixed powder at 350°C or less in an air atmosphere. The amounts of raw materials are 0.7-5% by mass of Li raw material, 8-60% by mass of Nb raw material, and 1.0-30% by mass of P raw material, which are dry-mixed with respect to the obtained mixed powder, to produce a solid electrolyte powder with a crystallite size of 100 nm or less (preferably amorphous, hereinafter referred to as "amorphous"). The contents overlapping with those described in [1. Solid electrolyte powder] above will be omitted below. The mass% expression configuration and molar ratio expression configuration described in [1. Solid electrolyte powder] can also be applied to the amounts of Li raw material, Nb raw material, and P raw material as the amounts charged in the manufacturing method of the solid electrolyte powder. Also, the amount of non-oxygen remainder (10 mass% or less) described in [1. Solid electrolyte powder] can be applied to the manufacturing method of the solid electrolyte powder.

[0083] As the Li raw material, it is preferable to prepare lithium compounds such as lithium hydroxide, lithium oxide, and lithium nitrate. The Li raw material is preferably lithium oxide. The reason is that lithium oxide is classified as a network modifier oxide of glass-forming oxides, and the intermediate oxide Nb2O5 is likely to become amorphous when coexisting with lithium oxide, making it easy to obtain a solid electrolyte powder with a crystallite size of 100 nm or less.

[0084] It is preferable to prepare niobium oxides such as NbO, NbO2, and Nb2O5·nH2O as the Nb raw material. It is preferable to use Nb2O5·nH2O, which is an intermediate oxide of glass-forming oxides, because the solid electrolyte powder obtained tends to be amorphous and the crystallite size is 100 nm or less.

[0085] As the P raw material, it is preferable to prepare phosphorus compounds such as diphosphorus pentoxide, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, etc. Diphosphorus pentoxide (P2O5) is preferable as the P raw material. Diphosphorus pentoxide is a network-forming oxide of glass-forming oxides, and the mixed powder tends to become amorphous, making it easy to obtain a solid electrolyte powder with a crystallite size of 100 nm or less.

[0086] A preferred example of the combination of the respective raw materials is a combination in which the Li raw material is lithium oxide, the Nb raw material is hydrous niobium oxide, and the P raw material is diphosphorus pentoxide.

[0087] (Weighing process) The Li raw material, the Nb raw material, and the P raw material are weighed out so that the resulting solid electrolyte powder satisfies the above-mentioned composition expressed in mass % and / or composition expressed in molar ratio.

[0088] (Mixed powder acquisition process) In the method for producing a solid electrolyte powder according to the present embodiment, raw materials containing solid substances Li, Nb, and P are mechanically mixed. The mechanical mixing can be performed by a method of pulverizing and mixing using a pulverizer such as a dry ball mill.

[0089] The time for pulverization and mixing is preferably set in the range of 1 to 50 hours so that both substances are thoroughly mixed. The particle size of the mixed powder is preferably 5 to 50 μm as described above.

[0090] The atmosphere in the mixing vessel is preferably an inert gas atmosphere such as argon or nitrogen, while having a dew point of -20°C or less (preferably -40°C or less). If the dew point of the atmosphere is -20°C or less, the reaction between the moisture in the atmosphere and the P raw material can be suppressed. As a result, the generation of phosphoric acid, which can be an obstacle when obtaining an amorphous material, can be suppressed, and a solid electrolyte powder with a crystallite size of 100 nm or less can be obtained. The dew point of the atmosphere in the mixing vessel may be set to, for example, -100°C or more, -90°C or more, or -80°C or more.

[0091] (Firing process) The mixed powder obtained by the mechanical mixing is fired to synthesize an amorphous powder containing Li, Nb, and P. The firing atmosphere is preferably air. The firing temperature is preferably in the range of 150 to 350°C. The lower limit of the firing temperature is preferably 200°C. The firing time may be set in the range of 0.5 to 10 hours, for example. The rate of temperature rise from room temperature to the firing temperature can be 5 to 15°C / min.

[0092] (Crushing process) The fired powder obtained in the firing step may be further pulverized, preferably to a particle size of 5 to 50 μm as described above.

[0093] <<Method for producing coating solution for coating positive electrode active material with first solid electrolyte (wet method)>> FIG. 9 is a flow diagram when the first solid electrolyte is coated on the positive electrode active material using the coating liquid according to the present invention.

[0094] The coating liquid may be produced as follows. That is, in the method of producing an aqueous solution (coating liquid) containing niobium polyacid ions, lithium ions, and phosphate ions of the present invention, hydrous niobium oxide is used as the starting material for niobium. Hydrous niobium oxide and LiOH are dissolved in water to obtain an aqueous solution containing niobium polyacid ions and lithium, and then phosphate ions are added to the aqueous solution to obtain an aqueous solution containing niobium polyacid ions, lithium ions, and phosphate ions. This step is also referred to as a coating liquid production step. Hereinafter, for wet processes, element names or compound names will be used instead of element symbols.

[0095] In the present invention, an aqueous coating liquid may be used to coat the positive electrode active material powder with the first solid electrolyte 1. As the aqueous lithium niobate coating liquid, an aqueous lithium niobate precursor solution using polyacid ions having excellent chemical stability is used.

[0096] In addition, the niobium polyacid ions once solubilized in the alkaline solution maintain the form of a polyacid even when phosphoric acid is added and the pH of the system is lowered to about 4. The aqueous solution of the present invention containing niobium polyacid ions, lithium ions, and phosphate ions contains niobium in the form of a polyacid and therefore has excellent storage stability.

[0097] The reason why the coexistence of niobium polyacid ions and phosphate ions in an aqueous lithium ion solution suppresses the increase in the specific surface area of ​​the coated positive electrode active material is unclear at present, but the inventors speculate as follows.

[0098] That is, the presence of phosphate ions in an aqueous solution containing niobium polyacid ions, lithium ions, and phosphate ions improves the wettability of the aqueous solution to the surface of the positive electrode active material. The action of phosphate ions in an aqueous solution with excellent storage stability changes the double layer structure at the interface, thereby changing the structure of the coating layer. Alternatively, the use of stable polyacid ions can suppress gas generation, which is one cause of pores, and further, a small amount of phosphate ions contained in the coating layer suppresses the generation of pores in the coating layer during drying.

[0099] Therefore, by using the coating liquid of the present invention, a high coverage rate and uniform coating can be achieved.

[0100] [Nb source] Since anhydrous niobium oxide (Nb2O5) is poorly soluble in water, the manufacturing method of the present invention uses amorphous, water-soluble niobium oxide as the Nb source. Niobium oxide hydroxide is a substance represented by the general formula Nb2O5·nH2O (n is not 0, for example, 3≦n≦16).

[0101] [Polyacid ion] Polyacids are anionic species formed by the condensation of oxoacids, and polyacids of transition metal elements can be considered to be molecular ionic species of metal oxides. When there is only one type of metal element, they are called isopolyacids, and when there are multiple metal elements, they are called heteropolyacids.

[0102] The potential-pH diagram for niobium has not yet been established, but since niobium hydroxide precipitates in the neutral region, it is believed that solid phases such as Nb(OH)5 or HNbO3 are stable species in this pH region.

[0103] When an alkali is added to an aqueous solution containing these solid phases to raise the pH of the system, excess OH - The presence of ions causes niobium to react with e.g. Nb(OH)6 - and NbO3 - etc. If the pH of the system is further increased, the soluble niobium oxide is thought to take on various condensation states depending on the pH of the system, but in this specification, the niobium oxide solubilized on the alkaline side is considered to become niobium polyacid ions collectively. Note that the niobium polyacid ions once solubilized on the alkaline side maintain the form of a polyacid even when the pH of the system is lowered to about 4 by adding phosphoric acid.

[0104] The aqueous solution of the present invention containing niobium polyacid ions, lithium ions and phosphate ions has excellent storage stability because it contains niobium in the form of a polyacid. The form of niobium may be a soluble polyacid ion, and the structure is not particularly limited.

[0105] The fact that niobium in an aqueous solution is in the form of a polyacid ion can be confirmed by FT-IR measurement. When niobium in an aqueous solution is in the form of a polyacid ion, the FT-IR spectrum is at a wave number of 850 cm -1 ±20cm -1 An absorption peak due to Nb-O bonds is observed near the

[0106] [Lithium hydroxide] In the manufacturing method of the present invention, lithium hydroxide (LiOH) is used as a Li source. LiOH may be either anhydrous or hydrated. In the manufacturing method of the present invention for preparing an aqueous solution containing niobium polyacid ions, lithium ions, and phosphate ions, LiOH is first added to an aqueous solution containing niobic acid to dissolve the niobic acid.

[0107] LiOH is itself a strong alkali, so when LiOH is added to an aqueous solution containing niobic acid, the pH of the system rises, dissolving the niobium oxide and forming a stable polyoxygen ion of niobium. Hydrogen peroxide is then added to the alkaline aqueous solution containing the polyoxygen ion of niobium and lithium ions, but the effect of hydrogen peroxide will be described later.

[0108] In the aqueous solution of the present invention containing niobium polyacid ions, lithium ions, and phosphate ions, the molar ratios of Li, Nb, and P are Li:Nb:P=x:y:z (x+y+z=100), where x is 15-50, y is 5-65, and z is 5-65.

[0109] In the aqueous solution containing the polyacid ions of niobium, lithium ions, and phosphate ions of the present invention, the niobium is considered to be mainly in the form of a relatively stable polyacid. The addition of hydrogen peroxide to the aqueous solution further improves the storage stability. Since the aqueous solution of the present invention does not contain organic matter, a coating layer with a low volume resistivity can be finally obtained.

[0110] [Phosphate ion] The major technical feature of the present invention is that phosphate ions are made to coexist in an aqueous solution containing niobium polyphosphate ions and lithium ions. The source of phosphate ions is water-soluble phosphoric acid (PO4 3- ) salts can be used. Phosphoric acid is a tribasic acid that dissociates in three stages in an aqueous solution, and therefore can exist in various forms in the aqueous solution, such as phosphate ion, monohydrogen phosphate ion, dihydrogen phosphate ion, and pyrophosphate ion, but the form is determined by the pH of the aqueous solution, not by the type of chemical used as the phosphate ion source, and therefore the above ions containing a phosphate group are collectively referred to as phosphate ions.

[0111] In terms of the content of phosphate ions in an aqueous solution containing niobium polyphosphate ions, lithium ions, and phosphate ions, according to the above molar ratio expression, z is 5 to 65, and preferably 10 to 45, as described above. If z is 5 or more, the effect of adding phosphate ions is sufficient. If z is 65 or less, the effect of adding phosphate ions does not become saturated.

[0112] The sum of the contents of lithium, niobium and phosphorus in the aqueous solution containing niobium polyacid ions, lithium ions and phosphate ions is preferably 1% by mass or more and 20% by mass or less. More preferably, it is 3% by mass or more and 10% by mass or less. If the sum of the contents of lithium, niobium and phosphorus is 1% by mass or more, it is not necessary to increase the amount of the aqueous solution containing niobium polyacid ions, lithium ions and phosphate ions to obtain the required thickness of the coating layer, and it is not necessary to increase the amount of water, which is advantageous in terms of cost. If the sum of the contents of lithium, niobium and phosphorus is 20% by mass or less, the viscosity of the aqueous solution containing niobium polyacid ions, lithium ions and phosphate ions is appropriate, and clogging of thin piping of the device used for the coating process can be suppressed.

[0113] The amount of impurity elements other than lithium, niobium, phosphorus, oxygen, and hydrogen in the aqueous solution containing niobium polyacid ions, lithium ions, and phosphate ions is preferably 10% by mass or less. More preferably, it is 1% by mass or less. A specific example of an impurity element is nitrogen, and the amount of nitrogen is preferably 0.1% by mass or less, 0.01% by mass or less, 0.001% by mass or less, 0.0001% by mass or less (1 ppm) or less, and 0.1 ppm or less, in that order. In addition, carbonate ions and the like are considered as unavoidable impurities. Note that the impurities referred to here refer to impurities contained in the evaporation residue when the precursor aqueous solution is evaporated to dryness at 200°C.

[0114] [hydrogen peroxide] The aqueous solution of the present invention may further contain hydrogen peroxide to improve storage stability. In this case, hydrogen peroxide is preferably added so that the concentration of the aqueous solution is 0.01% by mass or more and 10% by mass or less. If the concentration of hydrogen peroxide is 0.01% by mass or more, the generated niobium polyacid can be prevented from reacting with hydroxide ions and decomposing. If the concentration is 10% by mass or less, the generated niobium polyacid can be prevented from reacting with hydrogen peroxide and decomposing.

[0115] The molar ratio (POA / Nb) of the amount of hydrogen peroxide and niobium added is preferably in the range of 0.1 to 1. A ratio of 0.1 or more is advantageous in avoiding the reaction of niobium polyacid with hydroxide ions and decomposition. A ratio of 1 or less makes it easier for the generated niobium polyacid to react with hydrogen peroxide and decompose.

[0116] From the viewpoint of reactivity, the hydrogen peroxide is preferably added after dissolving hydrous niobium oxide with LiOH to form stable polyoxygen ions of niobium. Note that the addition of the phosphate ions and the hydrogen peroxide in this section may be performed in any order.

[0117] Here, the added hydrogen peroxide decomposes over time, but it is preferable that the aqueous solution contains 0.01% by mass or more and 6.7% by mass or less of hydrogen peroxide. If the hydrogen peroxide content is 0.01% by mass or more, the effect of maintaining the stability of the precursor aqueous solution can be adequately exhibited. Also, if the hydrogen peroxide content is 6.7% by mass or less, the effect of adding hydrogen peroxide does not become saturated.

[0118] In addition, the ratio of the number of moles of hydrogen peroxide to 1 mole of niobium (POC / Nb), calculated from the concentration of hydrogen peroxide and the concentration of niobium present in the aqueous solution, is preferably in the range of 0.01 to 1. Within the above range, not only is the effect of adding hydrogen peroxide not saturated, but also, when used as a coating solution, the positive electrode active material is not dissolved. If hydrogen peroxide is present in an appropriate amount, not too small, it is possible to suppress the reaction of the polyacid of niobium with hydroxide ions and decomposition. A more preferable range of POC / Nb is 0.05 to 0.5.

[0119] [pH] In the manufacturing method of the present invention, the pH of the aqueous solution when forming the niobium polyacid ion is almost automatically determined by the amount of LiOH, which is a strong alkali, the amount of phosphoric acid, and the amount of hydrogen peroxide, so there is no need to adjust the pH, but it is alkaline, 7.5 to 12.5. Since the niobium polyacid ion is stably formed, the pH is more preferably 9.0 to 12.0. When phosphoric acid is added to the solution containing this niobium polyacid and lithium, the pH of the system decreases, but it has been confirmed that the niobium polyacid exists stably at a pH of 3 or more. The pH of the solution to which phosphoric acid is added is preferably 12.5 or less. More preferably, it is 12 or less. The pH value here is a value measured using a glass electrode with a pH meter equipped with a temperature compensation electrode, calibrated with an appropriate buffer solution according to the pH range to be measured based on JIS Z8802.

[0120] The method for coating a positive electrode active material with a solid electrolyte using a coating liquid according to this embodiment mainly has the following configuration. The following configuration is also technically significant as a method for producing a coating in which a positive electrode active material is coated with a solid electrolyte. Each example described in this specification is applicable to the contents described in this paragraph. A phosphate ion addition process in which phosphate ions are added to an aqueous solution containing niobium polyacid ions and lithium A coating process in which the aqueous solution obtained in the adding process is brought into contact with the positive electrode active material, and the surface of the positive electrode active material is coated with the solid electrolyte. When the molar ratio of Li, Nb, and P in the aqueous solution obtained by the addition step is Li:Nb:P=x:y:z (x+y+z=100), x is 15-50, y is 5-65, and z is 5-65. Through the above steps, at least one of the following solid electrolytes is coated on the surface of the positive electrode active material, thereby obtaining a coated body. i) the solid electrolyte contains 0.7 to 5 mass% Li, 8 to 60 mass% Nb, and 1.0 to 30 mass% P; The content of the non-oxygen remainder other than oxygen (O) in the remainder is 10 mass% or less with respect to the solid electrolyte, A solid electrolyte having a crystallite size of 100 nm or less. ii) When the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 15-50, y is 5-65, and z is 5-65; A solid electrolyte having a crystallite size of 100 nm or less.

[0121] A specific embodiment of the coating step will be described later in Example 10. The positive electrode active material mixing step in Fig. 9 is not limited to a specific method as long as the coating liquid and the positive electrode active material are mixed. The same applies to the drying step, and there is no specific limit to the method.

[0122] In this section, the case where the positive electrode active material powder is coated with the first solid electrolyte 1 using an aqueous coating liquid has been described. On the other hand, the solid electrolyte powder may be obtained from this coating liquid. The method mainly has the following configuration. Each example described in this specification is applicable to the contents described in this paragraph. A phosphate ion addition process in which phosphate ions are added to an aqueous solution containing niobium polyacid ions and lithium A drying process in which the aqueous solution obtained in the addition process is dried to obtain solid electrolyte powder. When the molar ratio of Li, Nb, and P in the aqueous solution obtained by the addition step is Li:Nb:P=x:y:z (x+y+z=100), x is 15-50, y is 5-65, and z is 5-65. Moreover, like the solid electrolyte powder obtained by the dry process, this solid electrolyte powder may be used to fabricate an all-solid-state battery cell.

[0123] <Modifications, etc.> Although one aspect of the present invention has been described above, the above disclosure shows one exemplary aspect of the present invention. In other words, the technical scope of the present invention is not limited to the above exemplary aspect, and various modifications are possible without departing from the gist of the present invention. In addition, the above disclosure can be arbitrarily selected and combined with the following modified examples. EXAMPLES

[0124] The present invention will be specifically described below using examples, but the present invention is not limited to the following examples in any way.

[0125] Dry-type Examples: Comparative Example 1, Examples 1 to 9 In each example, lithium oxide (Wako Pure Chemical Industries, Li2O), hydrous niobium oxide (HC Starck, Nb2O5·nH2O, Nb2O5 content 56.4%), and diphosphorus pentoxide (Wako Pure Chemical Industries, P2O5) were weighed out as the Li raw material, Nb raw material, and P raw material, respectively, in the amounts shown in Table 1 below. The weighed Li raw material, Nb raw material, and P raw material were mixed together with zirconia balls Φ10 mm in a planetary ball mill (Fritsch, P-7) in an argon atmosphere with a dew point temperature of -60°C for 24 hours at 380 rpm to obtain a mixed powder. [Table 1]

[0126] The mixed powder was placed in a hot air drying furnace and heat-treated at a firing temperature of 200°C for 5 hours to obtain a fired powder. The fired powder was pulverized with zirconia balls Φ10mm in a planetary ball mill (Fritsch, P-7) while stirring at 380 rpm in air for 5 hours to obtain a solid electrolyte powder for each example.

[0127] In Comparative Example 1, the P raw material was not used, and the Li raw material and the Nb raw material were weighed in the amounts shown in Table 1, and other than that, a solid electrolyte powder was obtained in the same manner as in each of the Examples.

[0128] The solid electrolyte powder obtained in each example was subjected to ICP measurement, and the constituent elements of the solid electrolyte powder were quantitatively analyzed. The contents of niobium, lithium, and phosphorus obtained by the measurement are shown in Table 2. The ICP measurement method is as follows. [Table 2]

[0129] After the pulverization step in each example, 0.1 g of the sintered powder (solid electrolyte powder) obtained was weighed out. 1 mL of hydrofluoric acid having a concentration of 46% by mass was added to the powder sample to decompose the sample. The decomposition solution was adjusted to a constant volume using a 100 mL measuring flask and diluted 100 times with 5% by mass hydrochloric acid. The concentrations of the constituent elements of the solid electrolyte powder, including niobium, lithium, and phosphorus, in the diluted solution were measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES, Agilent Technologies, Inc. CP-720).

[0130] The nitrogen content in the solid electrolyte powder obtained in each example was analyzed using a nitrogen analyzer (EMGA-920, manufactured by Horiba, Ltd.). The carbon content in the solid electrolyte powder obtained in each example was analyzed using a trace carbon / sulfur analyzer (ETMA-U510, manufactured by Horiba, Ltd.). The content of elements other than O (i.e., non-oxygen elements) among the remainders other than lithium, niobium, and phosphorus obtained from the above ICP measurement, nitrogen content, and carbon content measurement results was 1 mass% or less in all examples.

[0131] FIG. 5 is a diagram showing the composition ratios of Li, Nb, and P in the solid electrolyte powder obtained in each example, expressed in molar ratio.

[0132] The volume-based cumulative 50% particle size (D50) of the solid electrolyte powder obtained in each example was measured. The measurement results are shown in Table 2. In this specification, the volume-based cumulative 50% particle size (D50) is measured as follows. The particle size distribution of the obtained solid electrolyte powder was measured using a laser diffraction particle size distribution measuring device (HELOS H3758 & RODOS, manufactured by Nippon Laser). The dispersion method was air flow dispersion (nitrogen), the dispersion pressure was 5 bar, and the focal length was 200 mm.

[0133] Here, an all-solid-state electrochemical cell was fabricated in which the solid electrolyte (first solid electrolyte) of the test material and the sulfide-based solid electrolyte (second solid electrolyte) were adjacent to each other, and the decomposition voltage resulting from the oxidation reaction of the test material was determined in accordance with the evaluation method disclosed in Patent Document 2. Specifically, the experiment was carried out as follows. <1. Preparation of the mixture> The solid electrolyte powders of the comparative examples and examples and the stainless steel (SUS316) powder were weighed out to give a volume ratio of 50:50. Then, the materials were mixed in a mortar to prepare a composite mixture. 2. Preparation of electrochemical cell 57 mg of argyrodite-type sulfide solid electrolyte (Li6PS5Cl) was placed in the insulating outer cylinder. This was then pressed at a pressure of 80 MPa to obtain a second solid electrolyte. Next, 20 mg of the solid electrolyte of each of the examples and comparative examples was placed on the second solid electrolyte, and the mixture was pressed at a pressure of 80 MPa to form a first solid electrolyte. Next, 20 mg of the composite mixture of the example and comparative example was poured onto the first solid electrolyte and pressure-molded at a pressure of 360 MPa to form a composite. Next, metal In (200 μm thick), metal Li (300 μm thick), and metal In (200 μm thick) were laminated in this order under the second solid electrolyte (opposite side to the first solid electrolyte). This was then press-molded at a pressure of 80 MPa to form a counter electrode member with a three-layer structure of In / Li / In. Next, stainless steel plate current collectors were placed on the top and bottom of the laminate, and current collecting leads were provided. In this manner, an electrochemical cell was prepared.

[0134] FIG. 6 is a diagram showing the composition ratios of Li, Nb, and P in the composition expressed by molar ratio of the solid electrolyte powder obtained in each example, as well as the decomposition voltage as numerical values.

[0135] The electrochemical evaluation method is as follows. The electrochemical cell was placed in a thermostatic bath at 25°C. The voltage stability was evaluated by sweeping the voltage from the open circuit voltage of the electrochemical cell to 6.0 V (vs In-Li) (synonymous with 6.6 V (vs Li)) using a potentio / galvanostat (Prinston VersaSTAT4), an electrochemical measurement device, and measuring the reaction current. When the voltage on the working electrode side of the electrochemical cell is swept toward the oxidation side, a current resulting from a non-Faraday reaction not involving the transfer of electrons and a minute current resulting from a side reaction of adsorbed water and impurities flows. The current up to 4.0 V (vs Li) was relatively small, less than 10 μA, and the increase rate was less than 10 μA / V, so it was determined to be a current resulting from a side reaction. When a voltage exceeding 4.0 V is applied, a point appears where the current value increases; this reaction is the current associated with the decomposition reaction. In this test, the decomposition voltage was defined as the voltage at which a current of 15 μA flowed.

[0136] Figure 7 shows the potential (unit: V(vs Li / Li + ) on the horizontal axis and current value (in μA) on the vertical axis.

[0137] The method for measuring ionic conductivity is as follows. 0.2 g of the powder sample according to each example was put into a cylindrical container with a diameter of 10 mm and pressed at 180 MPa by a press to obtain a pressed powder body. The obtained pressed powder body was pressurized again at 300 MPa using a CIP molding machine (CPP-PS200A and CPP28-300B manufactured by NBE System Co., Ltd.), and silver paste was applied to both sides to obtain a sample for measuring ionic conductivity. For the obtained sample, under a nitrogen atmosphere at a temperature of 30 °C, using an impedance analyzer (ZENNIUM manufactured by ZAHNER), ionic conductivity was measured by the AC impedance method in the range of 0.1 Hz to 4 MHz with an amplitude voltage of 500 mV. Then, from the Cole-Cole plot (complex impedance plane plot) of the measured values, the resistance value of the sample according to the example was obtained, and the ionic conductivity was calculated from the obtained resistance value. The calculated value of the ionic conductivity is described in Table 2 above. When the ionic conductivity is 5.0×10 -10 (S / cm) or more, it is very good. When the ionic conductivity is less than 5.0×10 -10 (S / cm) and 5.0×10 -11 (S / cm) or more, it is described as good.

[0138] XRD measurement was performed on the solid electrolyte powder according to each example under the following measurement conditions. Figure 8 is a plot with 2θ (unit: °) on the horizontal axis and intensity (cps) on the vertical axis in the evaluation of crystallinity in each example. <XRD Measurement Conditions> Measuring device: XRD-6100 (manufactured by Shimadzu Corporation) Tube target: Cu (measured at the wavelength of Kα1) Tube voltage: 40 kv Tube current: 30 mA Divergence slit: 1.0° Scattering slit: 1.0° Receiving slit: 0.3 mm Step width: 0.02° / step Measurement time: 0.60 sec

[0139] 8, in the XRD spectrum of the solid electrolyte powder according to each example, a halo with a half-width of 2θ:2° or more was observed in the region of 2θ:15° to 40°, confirming that the solid electrolyte powder according to each example was amorphous.

[0140] As shown in Table 2, the decomposition voltage was higher in each Example than in Comparative Example 1. As a result, each Example provided an all-solid-state battery cell and a lithium-ion secondary battery that achieved both high lithium ion conductivity and high decomposition voltage. In other words, it was found that the solid electrolyte powder and the manufacturing method thereof according to each Example can achieve both high lithium ion conductivity and high decomposition voltage.

[0141] Wet Method Examples: Comparative Example 2 and Example 10 In order to coat the positive electrode active material with the first solid electrolyte, the following first solid electrolyte coating solution was prepared and used to coat the positive electrode active material. The first solid electrolyte coating solutions of Comparative Example 2 and Example 10 were prepared as follows. 41g of lithium hydroxide (LiOH, manufactured by Wako Pure Chemical Industries, Ltd.) and 125g of hydrous niobium oxide (Nb2O5·nH2O, manufactured by HC Starck, Nb2O5 content 56.4%) were mixed with 734g of water and stirred at a stirring speed of 200 rpm. After that, the temperature was raised to 70°C at a temperature rise rate of 0.75°C / min., and then held at 70°C for 7h. After holding, 29g of hydrogen peroxide was added and filtered to obtain a lithium niobate solution of Comparative Example 2. 49g of water was added to 35g of the obtained lithium niobate solution to obtain a coating solution of Comparative Example 2. In addition, 48g of water and 1.1g of phosphoric acid (Wako Pure Chemical Industries, phosphoric acid concentration 85% solution) were added to 35g of the lithium niobate solution to obtain a coating solution of Example 10. The coating solution obtained in each example was subjected to pH measurement and ICP measurement. The values ​​obtained by the measurements are shown in Table 3. The components of the coating solution were analyzed using an inductively coupled plasma atomic emission spectrometer (ICP-AES, Agilent Technology 700 Series). 0.1 g of sample was taken from the precursor solution and weighed, and 15 mL of pure water and 5 mL of hydrochloric acid were added to it, heated, and then allowed to cool. 2 mL of hydrogen peroxide was added and allowed to cool, after which the liquid volume was adjusted to 100 mL and ICP-AES analysis was performed. The moles of the present invention were calculated from the contents of niobium, lithium, and phosphorus obtained by the quantitative analysis using ICP. Furthermore, to confirm whether the niobium in the aqueous solutions of Comparative Example 2 and Example 10 is a polyacid ion, Fourier transform infrared spectroscopy (FT-IR) was performed using a NICOLET7600 manufactured by Thermo Fisher Scientific. In order to remove the low wavenumber peak of the water solvent, water was used for background measurement, and the measurement was performed by the attenuated total reflection (ATR) method. A germanium prism was used for the measurement, and the angle of incidence was set to 45°. When the aqueous solutions of Comparative Example 2 and Example 10 were subjected to FT-IR measurement, the peak at a wavenumber of 850 cm was observed. -1 ±20cm -1 An absorption peak due to Nb-O bonds was observed near the peak, and it is believed that the solubilized hydrous niobium oxide exists in the form of niobium polyacid ions. The FT-IR spectra of the aqueous solutions obtained in Comparative Example 2 and Example 10 are shown in Figure 10. [Table 3]

[0142] The coating liquids of Comparative Example 2 and Example 10 were dried in the air at 200°C to obtain solid electrolyte powders. The powders (solid electrolyte powders) of Comparative Example 2 and Example 10 obtained after drying in the air were subjected to quantitative analysis of the constituent elements of the solid electrolyte powder, nitrogen content, and measurement of the cumulative 50% particle size (D50) based on volume of the solid electrolyte powder in the same manner as in Example 1. The results are shown in Table 3. Measurements of decomposition voltage and ionic conductivity were also performed. The values ​​obtained by the measurements are shown in Table 4. [Table 4]

[0143] XRD measurements were performed on the powders of Comparative Example 2 and Example 10 obtained after air drying in the same manner as in Example 1. As a result, a halo with a half-width of 2θ:2° or more was observed in the XRD spectrum of the solid electrolyte powder of each example in the region of 2θ:15° to 40°. This confirmed that the solid electrolyte powder of each example was amorphous.

[0144] Next, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The positive electrode active material powder was 4Sorb US manufactured by Yuasa Ionics Corporation, and the BET specific surface area was 0.538 m2 by the BET single point method. 2 / g. The first solid electrolyte was coated onto the positive electrode active material powder using the coating liquids of Comparative Example 2 and Example 10. The coating method was as follows. 40 g of the positive electrode active material powder was mixed with 20 g of the solution of Comparative Example 2 and Example 10 obtained above, and coated using a coating device (JD-1 manufactured by Kawata) (positive electrode active material mixing step, drying step). The coating conditions were as follows. Slurry feed rate: 3mL / min. Dispersion air pressure: 500kPa Dispersion air temperature: 200℃ Dry air temperature: 135℃ Drying blower air volume: 900L / min. Classification blower air volume: 890L / min.

[0145] The coverage of the positive electrode active material powder with the first solid electrolyte was calculated based on the amount of elements measured using an XPS (JPS-9200 manufactured by JEOL Ltd.). The calculation formula is as shown in the following formula 1. The calculated coverage is shown in Table 5. Coverage rate (%) = (Nb + P) / (Ni + Co + Mn + Nb + P) × 100 (Equation 1) [Table 5]

[0146] In the positive electrode active material powder coated with the first solid electrolyte of this embodiment, it can be assumed that Nb and P, which are not contained in the positive electrode active material powder, are present only in the coating layer. In addition, the coating layer thickness of the positive electrode active material coated with the first solid electrolyte is expressed by the following formula 2 (the same applies to each of the following examples), assuming that Nb and P in the coating solution have changed to Nb2O5 and P2O5, respectively. If the Nb content in the coated positive electrode active material powder is a (mass%) and the P content is b (mass%), the mass ratio of Nb and P in the coating layer, c (mass%), is calculated from the atomic weights of Nb and P and the molecular weights of Nb2O5 and P2O5 by the following formula. The Nb content and P content are measured by the method described below. c = a × molecular weight of Nb2O5 / (atomic weight of Nb × 2) + b × molecular weight of P2O5 / (atomic weight of P × 2) (Equation 2) Furthermore, the specific surface area S (m 2 / g) and the density of the first solid electrolyte (g / cm 3 ), the average film thickness t (nm) of the coating layer is expressed by the following formula: Note that the number 10 on the right side of the following formula 3 is a conversion coefficient. t(nm)=10×C / (d×S) (Formula 3) The density of the first solid electrolyte is 4.13 g / cm 3 (The calculation was performed using the actual measured values ​​obtained by measuring the first solid electrolyte powder in Example 10 using a pycnometer MICRO-ULTRAPYC1200e manufactured by Anton Paar). The contents (mass %) of Nb and P in the positive electrode active material powder coated with the first solid electrolyte are measured as follows. 0.1 g of the positive electrode active material powder coated with the first solid electrolyte was weighed out. 1 mL of hydrofluoric acid with a concentration of 46 mass% was added to the powder sample to decompose the sample. The decomposition solution was adjusted to a constant volume using a 100 mL measuring flask and diluted 100 times with 5 mass% hydrochloric acid, and the concentrations of the constituent elements of the positive electrode active material powder, including niobium and phosphorus, in the diluted solution were measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES, CP-720 manufactured by Agilent Technologies, Inc.).

[0147] FIG. 11 is a schematic diagram of the cross-sectional structure of an electrochemical cell constructed to examine the discharge DCR increase rate in Comparative Example 2 and Example 10. The following electrochemical cells were fabricated using the positive electrode active material powder coated with the first solid electrolyte using the coating liquid of Comparative Example 2 and Example 10. The direct current internal resistance (DCR) of the electrochemical cell was measured when the fabricated electrochemical cell was subjected to float charging at a constant voltage, and the discharge DCR increase rate was calculated to evaluate the deterioration of the electrochemical cell. Specifically, the experiment was performed as follows. A composite mixture was prepared by mixing 70 mg of the positive electrode active material coated with the first solid electrolyte, 30 mg of an argyrodite-type sulfide solid electrolyte (Li6PS5Cl) as the second solid electrolyte, and 3.1 mg of carbon as a conductive material in a mortar. 100 mg of argyrodite-type sulfide solid electrolyte (Li6PS5Cl) was placed in the insulating outer cylinder. This was then pressed at a pressure of 185 MPa to obtain a second solid electrolyte. Next, 10 mg of the composite mixture of the example and comparative example was poured onto the second solid electrolyte and pressure-molded at a pressure of 370 MPa to form a composite. Next, metal In (200 μm thick), metal Li (300 μm thick), and metal In (200 μm thick) were laminated in this order under the second solid electrolyte (opposite side to the first solid electrolyte). This was then press-molded at a pressure of 185 MPa to form a counter electrode member with a three-layer structure of In / Li / In. Next, stainless steel plate current collectors were placed on the top and bottom of the laminate, and current collecting leads were provided. In this manner, an electrochemical cell was prepared.

[0148] The battery evaluation method is as follows. The electrochemical cell was placed in a thermostatic bath at 55°C. Using a charge / discharge measuring device (Hokuto Denko HJ1001SD8), the voltage was swept from the open circuit voltage of the electrochemical cell to 3.83 V (vs In-Li) (equivalent to 4.45 V (vs Li)), and float charging was performed for 30 days. The DCR increase rate was calculated in the following manner. After adjusting the voltage of the electrochemical cell that had been float-charged for 30 days to 3.9 V (vs Li), it was discharged at 1 C (C: current value that can charge and discharge the cell capacity in 1 hour) for 10 seconds. The discharge DCR increase rate was calculated by subtracting the voltage at the start of the test (0 seconds) from the voltage at the end of the test (10 seconds) and dividing the value by the current value. The calculated discharge DCR increase rate is shown in Table 6. [Table 6] [Explanation of symbols]

[0149] 1. The first solid electrolyte 2. Second solid electrolyte 3. High-potential conductive material 4. Low-potential conductive material 31 Cathode active material 32 Conductive materials other than positive electrode active materials 41 Negative electrode active material 42 Conductive materials other than negative electrode active materials

Claims

1. A conductive material on a high potential side; a first solid electrolyte in contact with the conductive material on the high potential side; a second solid electrolyte in contact with the first solid electrolyte; a conductive material on a low potential side in contact with the second solid electrolyte; Equipped with The first solid electrolyte contains at least one of the following solid electrolytes (1) and (2) as a main component: The all-solid-state battery cell, wherein the second solid electrolyte contains a sulfide as a main component. (1) A solid electrolyte comprising 0.7 to 5 mass% Li, 8 to 60 mass% Nb, and 1.0 to 30 mass% P, the content of non-oxygen remainder other than oxygen (O) being 10 mass% or less relative to the solid electrolyte, and a crystallite size of 100 nm or less. (2) A solid electrolyte in which, when the molar ratio of Li, Nb, and P contained in the solid electrolyte is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, and z is 5 to 65, and the crystallite size is 100 nm or less.

2. The all-solid-state battery cell according to claim 1 , wherein the first solid electrolyte is the following (3) or (4): (3) The solid electrolyte contains 0.7 to 2.6% by mass of Li, 8 to 60% by mass of Nb, and 2.0 to 30% by mass of P, A solid electrolyte, in which, when the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 30 or less, the content of non-oxygen remainder other than oxygen (O) is 10 mass% or less relative to the solid electrolyte, and the crystallite size is 100 nm or less. (4) A solid electrolyte in which, when the molar ratio of Li, Nb, and P contained in the solid electrolyte is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 30, y is 5 to 65, and z is 5 to 65, and the crystallite size is 100 nm or less.

3. the high potential side conductive material includes a positive electrode active material and other conductive members, The all-solid-state battery cell according to claim 1 , wherein the positive electrode active material and the first solid electrolyte are in contact with each other, and the positive electrode active material and the second solid electrolyte are not in contact with each other.

4. the high potential side conductive material includes a positive electrode active material and other conductive members, The all-solid-state battery cell according to claim 1 , further comprising a coating formed by coating a surface of a particle of the positive electrode active material with the first solid electrolyte.

5. The solid electrolyte powder contains 0.7 to 5 mass % of Li, 8 to 60 mass % of Nb, and 1.0 to 30 mass % of P, The content of the non-oxygen remainder other than oxygen (O) in the remainder is 10 mass% or less with respect to the solid electrolyte powder, A solid electrolyte powder having a crystallite size of 100 nm or less.

6. The solid electrolyte powder contains 0.7 to 2.6 mass% Li, 8 to 60 mass% Nb, and 2.0 to 30 mass% P, 6. The solid electrolyte powder according to claim 5, wherein x is 30 or less when the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100).

7. The solid electrolyte powder according to claim 5 , wherein the content of the transition metal element in the non-oxygen remainder is 3 mass % or less based on the mass of the solid electrolyte powder.

8. When the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, and z is 5 to 65; A solid electrolyte powder having a crystallite size of 100 nm or less.

9. The solid electrolyte powder according to claim 8 , wherein the content of the non-oxygen remainder other than oxygen (O) in the remainder is 10 mass % or less based on the solid electrolyte powder.

10. The solid electrolyte powder according to claim 8, wherein x is 15 to 30, y is 5 to 65, and z is 5 to 65.

11. The solid electrolyte powder according to any one of claims 5 to 10, wherein the total mass percentage of Li, Nb, and P in the solid electrolyte powder is in the range of 25 to 65 mass percent.

12. The solid electrolyte powder according to any one of claims 5 to 10, wherein the particle size of the solid electrolyte powder is a volume-based cumulative 50% particle size (D50) obtained by a laser diffraction scattering type particle size distribution measurement device, and is 5 to 50 μm.

13. The solid electrolyte powder according to any one of claims 5 to 10, which is for use in an all-solid-state battery cell.

14. A conductive material on a high potential side; a first solid electrolyte in contact with the conductive material on the high potential side; a second solid electrolyte in contact with the first solid electrolyte; a conductive material on a low potential side in contact with the second solid electrolyte; Equipped with The first solid electrolyte contains the solid electrolyte powder according to any one of claims 5 to 10 as a main component, The all-solid-state battery cell, wherein the second solid electrolyte contains a sulfide as a main component.

15. A method for producing a solid electrolyte powder according to claim 5 or 8, A step of dry-mixing a Li raw material, a Nb raw material, and a P raw material in an inert atmosphere having a dew point of −20° C. or less to obtain a mixed powder; A firing step of firing the mixed powder at 350° C. or less in an air atmosphere; A method for producing a solid electrolyte powder having the above structure.

16. 16. The method for producing a solid electrolyte powder according to claim 15, wherein the Li raw material is lithium oxide, the Nb raw material is hydrous niobium oxide, and the P raw material is diphosphorus pentoxide.

17. A method for producing a solid electrolyte powder according to claim 5 or 8, a phosphate ion adding step of adding phosphate ions to an aqueous solution containing niobium polyacid ions and lithium; a drying step of drying the aqueous solution obtained by the adding step to obtain a solid electrolyte powder; having When the molar ratio of Li, Nb, and P in the aqueous solution obtained by the adding step is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, and z is 5 to 65.

18. a step of adding phosphate ions to an aqueous solution containing niobium polyacid ions and lithium to obtain an aqueous solution in which, when the molar ratio of Li, Nb, and P in the aqueous solution is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, and z is 5 to 65; a coating step of contacting the aqueous solution obtained by the above step with a positive electrode active material to coat the surface of the positive electrode active material with a solid electrolyte; having The method for producing a coating, wherein the solid electrolyte satisfies at least one of the following: i) the solid electrolyte contains 0.7 to 5 mass% Li, 8 to 60 mass% Nb, and 1.0 to 30 mass% P; The content of the non-oxygen remainder other than oxygen (O) in the remainder is 10 mass% or less with respect to the solid electrolyte, A solid electrolyte having a crystallite size of 100 nm or less. ii) When the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, and z is 5 to 65; A solid electrolyte having a crystallite size of 100 nm or less.

Citation Information

Patent Citations

  • All-solid lithium battery

    WO2007004590A1

  • Positive electrode material, and battery

    WO2020174868A1

Cited By

  • Nb complex aqueous solution, method for manufacturing positive electrode active material for all-solid-state lithium ion battery, method for manufacturing positive electrode for all-solid-state lithium ion battery, and method for manufacturing all-solid-state lithium ion battery

    JP7774761B1